2011
DOI: 10.5604/01.3001.0009.5540
|View full text |Cite
|
Sign up to set email alerts
|

Performance Management as Modern Approach to Employees’ Appraisal in Healthcare Entities

Abstract: The past twenty years are the time of fundamental changes in Polish economy. It transformed from centrally planned economy to free market one. This concerns almost all sectors also the healthcare one, where the changes have become more dynamic within the last decade. The main aims of the sector reform were to commercialize public entities and to increase the role of private healthcare providers. Presently, both of the objectives are almost fulfilled and because of that competition has increased. This requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The strengths and weaknesses of the employees are identified through the performance appraisal. In some organizations, the performance appraisal has led to the development of an educational policy (Buchelt, 2011). Results of the performance appraisal should be discussed in a case-by-case manner and its focus is placed on supervisor-employee communications.…”
Section: Feedback and Uses Of The Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The strengths and weaknesses of the employees are identified through the performance appraisal. In some organizations, the performance appraisal has led to the development of an educational policy (Buchelt, 2011). Results of the performance appraisal should be discussed in a case-by-case manner and its focus is placed on supervisor-employee communications.…”
Section: Feedback and Uses Of The Resultsmentioning
confidence: 99%
“…As to the performance appraisal indicators, the main point mentioned is to avoid using ambiguous indicators as they might give such indicators some room for individual judgment and bias (Rolle & Klingner, 2012). The indicators should be, as possible, quantitative, not qualitative and descriptive (Buchelt, 2011). It is similarly suggested that the indicators be developed by the contribution of the employees and timely communication (Vasset et al, 2011).…”
Section: Feedback and Uses Of The Resultsmentioning
confidence: 99%
See 3 more Smart Citations